PENGARUH PEMERIKSAAN INTERN KHUSUSNYA PENGENDALIAN INTERN TERHADAP KECURANGAN (FRAUD) PADA PT. BANK BUKOPIN CABANG DURI RIAU - Wuri Handayani (STMIK Mardira Indonesia, Bandung, 2015)
Fraud is an act that is contrary to the truth and done intentionally to get something that is not a right of the culprit, so may result in losses to the company. To overcome this problem we need a tool that is expected to help the company's management in addressing the issue of fraud, the internal audit of internal control in particular. Based on the calculations, especially with the Spearman rank correlation coefficient was calculated rs = 0.949. This means in particular the relationship between internal audit of internal control with fraud is very strong, positive and focused. While based on a table of values Rs (Spearman Rank) with N = 10 and alpha = 0.05 i.e. Rs table = 0.648, because Rs count a based on the calculations, especially with the Spearman rank correlation coefficient was calculated Rs = 0.949. This means in particular the relationship between internal audits of internal control with fraud is very strong, positive and focused. While based on a table of values Rs (Spearman Rank) with N = 10 and > Rs table (0.949 > 0.648), then Ho is rejected and Ha accepted. The result of the calculation is the determination coefficient Kd = 90.06 %, this means that the influence / contribution of internal audit of internal control, especially against fraud amounted to 90.06 % and the balance of 9.94 % is influenced by other factors such as economic conditions, competition companies and others Based on hypothesis testing, obtained t = 8.513, whereas according to the t distribution table obtained t table = 2.306. Based on the results of the study showed that t > t table (8.513 > 2.306), this means that Ho is rejected and Ha accepted. Furthermore, the hypothesis which says “There is a significant relationship and influence between internal audit of internal control, especially against fraud, on the PT. Bukopin Branch Duri in Riau, is acceptable. Keywords: Internal Examination, Internal Controls, Fraud Abstrak Kecurangan (fraud) merupakan suatu perbuatan yang bertentangan dengan kebenaran dan dilakukan dengan sengaja untuk memperoleh sesuatu yang bukan merupakan hak pelakunya, sehingga dapat mengakibatkan kerugian pada perusahaan. Untuk mengatasi masalah tersebut dibutuhkan suatu alat yang diharapkan mampu membantu manajemen perusahaan di dalam mengatasi masalah kecurangan tersebut, yaitu pemeriksaan intern khususnya pengendalian intern. Berdasarkan hasil perhitungan diperoleh terutama dengan nilai koefisien korelasi Rank Spearman adalah rs hitung = 0,949. Ini berarti hubungan antara pemeriksaan intern khususnya pengendalian intern dengan kecurangan (fraud) sangat kuat, positif dan terarah. Sedangkan berdasarkan tabel nilai-nilai Rs (Rank Spearman) dengan N =10 dan a = 0,05 yaitu rs tabel = 0,648, karena rs hitung > rs tabel (0,949 > 0,648) maka Ho ditolak dan Ha diterima. Hasil perhitungan koefisien determinasi adalah Kd = 90,06%, hal ini berarti pengaruh/kontribusi pemeriksaan intern khususnya pengendalian intern terhadap kecurangan (fraud) sebesar 90,06% dan sisanya sebesar 9,94% dipengaruhi oleh faktor-faktor lain seperti keadaan ekonomi, persaingan perusahaan dan lain-lain. Berdasarkan pengujian hipotesisnya, diperoleh t hitung = 8,513, sedangkan menurut tabel distribusi t diperoleh t tabel = 2,306. Berdasarkan hasil penelitian menunjukkan bahwa t hitung > t tabel (8,513 > 2,306), hal ini berarti Ho ditolak dan Ha diterima. Selanjutnya hipotesis yang berbunyi “Terdapat hubungan dan pengaruh yang signifikan antara pemeriksaan intern khususnya pengendalian intern terhadap kecurangan (fraud)”, pada PT. Bank Bukopin Cabang Duri di Riau, dapat diterima. Kata Kunci : Pemeriksaan intern, Pengendalian intern, Kecurangan (fraud)